2015
DOI: 10.1155/2015/416480
|View full text |Cite|
|
Sign up to set email alerts
|

T Helper 17/Regulatory T Cell Balance and Experimental Models of Peritoneal Dialysis-Induced Damage

Abstract: Fibrosis is a general complication in many diseases. It is the main complication during peritoneal dialysis (PD) treatment, a therapy for renal failure disease. Local inflammation and mesothelial to mesenchymal transition (MMT) are well known key phenomena in peritoneal damage during PD. New data suggest that, in the peritoneal cavity, inflammatory changes may be regulated at least in part by a delicate balance between T helper 17 and regulatory T cells. This paper briefly reviews the implication of the Th17/T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 80 publications
0
22
0
Order By: Relevance
“…Besides components of the innate immunity, more recent studies performed using murine models demonstrated a main role of T helper 1 (Th1) cell response and of T lymphocytes expressing IL17A [ 19 21 ]. In these conditions, the presence of IL-6 is particularly relevant since it may shape the immune response in subacute-chronic conditions.…”
Section: Cellular Players Of Peritoneal Fibrosismentioning
confidence: 99%
See 1 more Smart Citation
“…Besides components of the innate immunity, more recent studies performed using murine models demonstrated a main role of T helper 1 (Th1) cell response and of T lymphocytes expressing IL17A [ 19 21 ]. In these conditions, the presence of IL-6 is particularly relevant since it may shape the immune response in subacute-chronic conditions.…”
Section: Cellular Players Of Peritoneal Fibrosismentioning
confidence: 99%
“…In these conditions, the presence of IL-6 is particularly relevant since it may shape the immune response in subacute-chronic conditions. IL-6, in combination with TGF- β , is the main cytokine involved in the T helper 17/regulatory T (Th17/Treg) balance [ 21 ]. The predominance of IL-6 favors the generation of Th-17 lymphocytes, which produce inflammatory cytokines.…”
Section: Cellular Players Of Peritoneal Fibrosismentioning
confidence: 99%
“…[15][16][17] Thus, chronic inflammatory damage of the peritoneal membrane can be modulated, at least in part, through regulation of the Th17/Treg balance. 18 Other cytokines are linked to specific PD-associated patient subgroups and characteristics. The chemokine CCL18 (also known as PARC, DC-CK1 and MIP-4) had originally been described to be predictive of encapsulating peritoneal sclerosis (EPS), but this finding was not confirmed by recent studies.…”
Section: Biomarker Research In the Context Of Chronic Peritoneal Inflmentioning
confidence: 99%
“…However, it is important to know that TGFβ is involved in the development and function of regulatory T cells (Tregs) [142][143][144], as adult mice deficient in TGFβ signaling exhibit a defective Treg phenotype with normal numbers, decreased suppressive function, and an incomplete TCR repertoire [145][146][147][148]. Tregs cells are extremely important for the maintenance of the peritoneal protection during PD [149], so treatments intended to block TGF-β signaling should take into account the complete cytokine environment and consider this side effect.…”
Section: Transforming Growth Factor (Tgf)-βmentioning
confidence: 99%